Simultaneous ground-based optical and SuperDARN observations of the shock aurora at MLT noon - Liu, Jianjun; Hu, Hongqiao; Han, Desheng; Yang, Huigen; Lester, Mark; Liu, JJ (reprint author), Polar Res Inst China, SOA Key Lab Polar Sci, Shanghai 200136, Peoples R China. (2015)
Using ground-based high temporal and spatial optical aurora observations, we investigated one fortuitous event to illustrate the direct responses of the fine structure auroral emission to interplanetary shock on 7 January 2005. During the shock impact to the magnetosphere, the Chinese Arctic Yellow River Station (YRS) equipped with all-sky imagers (ASIs) was situated at the magnetic local noon region (similar to 1210 MLT) in the Northern Hemisphere, while the SuperDARN CUTLASS Finland HF radar covering the field of view (FOV) of the ASIs at YRS had fine ionospheric plasma convection measurement. We observed that an intensified red aurora manifesting as a discrete emission band at a higher latitude responds to the shock impact gradually, which results in a distinct broadening of the dayside auroral oval due to the equatorward shifting of its lower latitude boundary after the shock arrival. In contrast, the green diffuse aurora, manifesting as a relatively uniform luminosity structure, reacts immediately to the shock compression, displaying prompt appearance in the southern edge of the FOV and subsequent poleward propagation of its higher latitude boundary. Simultaneously, the CUTLASS Finland radar monitored enhanced backscatter echo power and increased echo number, which coincided with intensified discrete aurora in approximately the same latitudinal region. Doppler velocity measurement showed moving ionospheric irregularities with generally enhanced line-of-sight (LOS) speed, but with prominent sunward flow in the polar cap and antisunward flow in both the eastern and western regions. The SuperDARN global ionospheric convection pattern clearly presented a large-scale plasma flow divided in four circulation cells, with two reversed flow cells nested in the noon sector of the polar cap. These direct observations strongly suggest that the prompt shock compression intensified the wave-particle interaction in the inner magnetosphere and enhanced the lobe magnetic reconnection rate at magnetospheric high latitude.